DAMPAK KENDARAAN LISTRIK TERHADAP LINGKUNGAN DAN SUMBERDAYA ALAM: ISU MUTAKHIR DALAM TRANSPORTASI BERKELANJUTAN - Rendi Ansah; Susilawati (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2022)
In recent years, attention to the negative impact produced by internal combustion engine vehicles on the environment has increased. Exhaust emissions and the use of fossil fuels are major challenges in the effort to achieve cleaner and more sustainable transportation. In this context, electric vehicles have become a promising solution to reduce air pollution and dependence on fossil fuels. From the results of previous studies show that in terms of cost electric vehicles are more efficient than oil-fueled vehicles. Based on the analysis of the impact of electric vehicles on the environment and natural resources, it can be concluded that electric vehicles have great potential to reduce greenhouse gas emissions and reduce dependence on limited natural resources. By replacing fossil fuel vehicles, electric vehicles can help reduce air pollution and contribute to climate change